(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
Collaborative management in the educational process is a management method that ensures the management of all processes involved in the educational process. This helps to increase the efficiency of learning, improve the process, and improve team spirit. Here we discuss the pedagogical mechanisms of collaborative organization in the management of a personal article in education.